First Patron's Day (Institutional Knowledge at Singapore Management University, 2001)
Singapore President S R Nathan (centre) and Singapore Management University management, faculty and staff at the first Patron’s Day celebrations. The event was held on 12 January 2001 at the Evans Road building.